Coupling of charge carriers with magnetic entropy for power factor enhancement in Mn doped Sn1.03Te for thermoelectric applications. Issue 24 (7th June 2018) - Acharya, Somnath; Anwar, Sharmistha; Mori, Takao; Soni, Ajay
Abstract : An approach for utilizing magnetism to try to enhance thermoelectric properties of Mn doped self-compensated Sn1.03 Te in context of its dilute magnetic nature. Abstract : Despite being a prospective thermoelectric (TE) material, SnTe has limited applicability due to the very high 'hole' concentration arising from 'Sn' vacancies. Engineering of multiple valence bands with the addition of extra 'Sn' and isovalent doping is a well-established strategy for enhancing TE properties. Here, we report a new approach utilizing magnetism to try to enhance the TE properties. The magnetic and TE properties of Mn doped self-compensated Sn1.03 Te were studied in the context of its dilute magnetic nature. A systematic (i) increment of magnetic moments and weak ferromagnetism leading to coupling of charge carriers, (ii) increase in effective thermal mass of charge carriers and (iii) overall enhancement in power factor have been observed and analyzed based on magnetization, heat capacity and high temperature transport measurements. At low temperatures, weak ferromagnetism is generated with Mn doping in otherwise diamagnetic Sn1.03 Te, thus giving system magnetic entropy and structural disorder, which leads to a modified TE transport. The enhancement in power factor for Sn0.93 Mn0.1 Te from Sn1.03 Te has been explained based on magnetic moments, the anomalous Hall effect, high effective thermal mass and magnetic entropy.